Os glides no português brasileiro - Evilazia Ferreira Martins (2011)
At last, what are the glides in the phonological system of Brazilian Portuguese? The main goal of this research is to investigate the answer for this question. It has been motivated by literature review that has already been made for these segments. It is also based in the reading of papers that describe, partly, their performance on phonology. This research permeates the study of its interaction with the stress pattern and syllabification, its behavior at the edges of morphemes and its distribution compared to the distribution of high vowels. It also permeates the interpretation of other segments such as the admission of geminate palatal (Wetzels, 2000) and the distribution of strong and weak /r/ (CAMÂRA JR. 1970; COLLISCHONN 1997, WETZELS, 1997). For this purpose, it is discussed and compared the analysis of Câmara Jr. (1953, 1969), Collischonn (1997) and Wetzels (1997, 2000a, b, 2009), which proposes the hypothesis of the underling glide, Câmara Jr. (1970), Leite (1974), Mateus (1982), Bisol (1989, 1994, 1996, 1999), Silva (1992) and Lee (1999), that proposes the hypothesis of the allophone glide, and Lopez (1979) argues that the underspecification of glides and high vowels. They are represented by the symbol V. The theories used in this work are Autossegmental Theory (GOLDSMITH, 1976), Feature Geometry (CLEMENTS, HUME, 1996) and Optimality Theory (PRINCE, SMOLENSKY, 1993).